(untitled) (Research, Society and Development, 2020)
In order to ensure the production and consumption of safe food, hygienic-sanitary measures should be developed and applied at all stages of the food chain. Legislation, developed throughout human history, advocates the quality conditions necessary for a food to be ingested without causing harm to people’s health. Therefore, as a way of assisting the teaching-learning process on the subject, the objective of this present article is to approach concepts, factors and aspects related to food security through the perspective of a critical pedagogical social trend of contents or historical-critical. For this, the methodology used was to carry out a basic research, characterized as bibliographic and exploratory. However, critical and conscious knowledge of the biological, chemical and physical dangers to which food is subjected and of disordered human action in the environment are important requirements for all institutional bodies and society as a whole to position themselves and demand that Food Security exists more and more concretely in people’s lives. And the new educational tools can assist in the process of building this knowledge.